2019
DOI: 10.1016/j.omto.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Reovirus and ATM Inhibitor Enhances Cell Death and Virus Replication in Canine Melanoma

Abstract: Oncolytic virotherapy using reovirus is a promising new anti-cancer treatment with potential for use in humans and dogs. Because reovirus monotherapy shows limited efficacy in human and canine cancer patients, the clinical development of a combination therapy is necessary. To identify candidate components of such a combination, we screened a 285-compound drug library for those that enhanced reovirus cytotoxicity in a canine melanoma cell line. Here, we show that exposure to an inhibitor of the ataxia telangiec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Combination treatment with SMAC mimetics and oncolytic VSVs enhanced tumor regression via a CD8 + T cell-dependent mechanism [ 94 ]. Moreover, anticancer activity was heightened when OVs were used in combination with either rapamycin [ 95 ], a small molecule inhibitor of ataxia telangiectasia mutated protein (ATM) [ 96 ], or an agonistic antibody targeting immunostimulant 4-1BB [ 97 ].…”
Section: Enhancing the Antitumor Effect By Combination Strategies Incmentioning
confidence: 99%
“…Combination treatment with SMAC mimetics and oncolytic VSVs enhanced tumor regression via a CD8 + T cell-dependent mechanism [ 94 ]. Moreover, anticancer activity was heightened when OVs were used in combination with either rapamycin [ 95 ], a small molecule inhibitor of ataxia telangiectasia mutated protein (ATM) [ 96 ], or an agonistic antibody targeting immunostimulant 4-1BB [ 97 ].…”
Section: Enhancing the Antitumor Effect By Combination Strategies Incmentioning
confidence: 99%
“…programmed cell death by intrinsic and extrinsic apoptosis or necroptosis (36,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). We did not observe an effect on r2Reovirus-induced cell death in the presence of a RIPK3 inhibitor (data not shown), suggesting that reovirus does not promote TNBC cell death by necroptosis.…”
Section: Downregulation Of Mapk/erk Signaling Can Lead To Apoptosis and Reovirus Can Inducementioning
confidence: 68%
“…Reovirus can induce cell death by apoptosis, necroptosis, cell cycle arrest or autophagy (36,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Reovirus can trigger apoptosis through recognition of viral nucleic acid by cellular pattern recognition receptors and subsequent activation of caspase 8, Bid cleavage, and disruption of the mitochondrial membrane.…”
Section: Introductionmentioning
confidence: 99%
“…When cells receive DNA damage, ATM is phosphorylated by the meiotic recombination 11/DNA repair protein Rad50/Nijmegen breakage syndrome 1 protein (MRN) complex, which is the upstream of ATM, and the phosphorylated ATM activates downstream Chk and p53 cascades [73][74][75][76][77]. Previous reports have shown that, in canine MM cell lines, ATM is phosphorylated via endogenous DNA damage [78]. In this study, p-ATM expression was increased in the dPDPN-knocked-down Mi cell line compared to the control siRNA-treated cells.…”
Section: Discussionmentioning
confidence: 99%